Diversity of Insect Pollinators on Dragon Fruit Plants (Hylocereus polyrhizus): (Diversity of Insect Pollinators on Dragon Fruit Plants (Hylocereus polyrhizus)) - Manap Trianto; Dirham Dirham (Otus Education: Jurnal Biologi dan Pendidikan Biologi, 2024)
Insect pollinators and plants have a mutually beneficial interaction. Insects get their needs in the form of pollen and nectar, while plants benefit from the pollination process. Dragon fruit (Hylocereus polyrhizus) is one of the fruit plants that is now starting to be widely cultivated in Indonesia after its first entry in the early 2000s. This study aims to analyze the diversity of visitor and pollinating insects and their role in fruit formation in dragon fruit plants. The research was conducted starting in October 2023. Sampling and observation of the diversity of visitor insects and pollinators were carried out in one of the gardens in Parigi Moutong Regency. Identification of visitor insects, and data analysis were carried out at the Biology Laboratory, Faculty of Teacher Training and Education, Tadulako University. Flower visitor insects found in this study were 7 species, namely Tetragonula clypearis, T. laeviceps, Scolia sp., butterflies E. Phaenareta and M. leda, D. thoracicus, and Stenogastrine sp. Five insect species have a role as pollinators on dragon fruit plants. Two insect species are predatory insects. Insect visitation activity on dragon fruit flowers was highest in the morning to afternoon and decreased in the afternoon.